2020
DOI: 10.2147/jir.s259035
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Anti-Inflammatory Effect of Pistacia Lentiscus in a Rat Model of Colitis</p>

Abstract: Introduction: The mastic tree (Pistacia lentiscus), belonging to the Anacardiaceae family, has anti-inflammatory and antioxidant properties. This study aims to assay the antiinflammatory effects of mastic in rats with colitis. Methods: Forty-eight male Sprague-Dawley rats were randomly divided into six groups of control, colitis without treatment, colitis with mastic (400 mg/kg/daily) administered orally or intra-rectally, colitis with prednisolone (5 mg/kg of body weight), and colitis with sesame oil for seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…40 g of mastic was dissolved in 200cc sesame oil (in boiling water). Then, the solution was mixed to become uniform [ 13 ]. The dose of mastic oil (400 mg/kg) was chosen based on traditional references [ 12 , 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…40 g of mastic was dissolved in 200cc sesame oil (in boiling water). Then, the solution was mixed to become uniform [ 13 ]. The dose of mastic oil (400 mg/kg) was chosen based on traditional references [ 12 , 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Zahouani et al (2020) underlined the anti-in ammatory effect of PLAE oral pre-treatment in acetic acid-induced ulcerative colitis, by reducing IL-6 production. Ostovan et al (2020) showed that PL mastic oil administered intra-rectally signi cantly decreased TNF-α level after 7 days of treatment in acetic acid-induced colitis. Our present nding are also in line with our previous results onethanol-induced gastric ulcer model showing that pre-treatment or treatment with PL fatty oil signi cantly reduced iNOS expression in the gastric mucosa.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, several other studies showed the bene t of Pistacia lentiscus (PL) extracts on ulcerative colitis. Recently, Ostovan et al (2020) demonstrated that Mastic Oil of PL signi cantly reduced the total colitis index, including in ammation severity, in ammation extent, and crypt damage scores. Razi et al (2000) suggested that supplementation with oleogum resin from PL delayed the onset and progression of the disease and helped prevent weight loss in the DSS model of colitis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, pistachio extracts and oil exhibit many beneficial health effects such as antimicrobial, anti-inflammatory, antidiabetic antitumour and antioxidant activities (Abidi et al, 2017;Catalani et al, 2017;Ostovan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%